PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP LOYALITAS PELANGGAN PADA FMS MOTOR DI PONTIANAK - B11108161, Andrianus (Jurnal Manajemen Update, 2013)
The purpose of this study is to investigate and analyze the influence of the Customer Relationship Management (continuity marketing, one to one marketing, patnering program) of customer loyalty on to the FMS Motor in Pontianak. Population in this study is the customer who makes a purchase vehicles yamaha motorcycle in FMS Motor in the year 2008-2011 which consisted of 5897 consumers. The number of samples taken in this study of 100 customer loyalty samples who makes a purchase vehicles yamaha motorcycle in FMS Motor in Pontianak. This study used a survey method and using program SPSS 16.0 in testing the validity, reliability, normality, multicollinearity, and heteroskedasitas, multiple linear regression, as well as simultaneous testing and Persial in determining the outcome of research. F test of fms Motor customers, the value of F count on columns F is 10,569 with a significance level of 0.000, where the figure is less than 0.05, which means that the independent variable has a positive and significant effect on the dependent variable. Based Persial test (t test) has been done can be concluded that for customer loyalty respondents FMS Motor of the three variables that have an impact on loyalty is partially patnering program variable (X3). While the variables that affect not partially is continuity marketing variable (X1) and one to one marketing variable (X2). Keywords: Continuity Marketing, One to One Marketing, Patnering Program and Loyalty